Pembelajaran IPS Berbasis Cerita Rakyat Asal Usul Desa Sokaraja untuk Menanamkan Karakter pada Siswa - Anjarwati, Titis; Maryono; Muhtar Sofwan Hidayat (STAI AL-AMIN, 2025)
This research was conducted at SD N 2 Sokaraja using qualitative methods. Qualitative methods are research that does not use mathematical, statistical or computer models. The aim of this thesis research is to: 1) To find out how social studies learning based on the folklore